Impact of foreign direct investment, money supply, exchange rate and international trade on economic growth in sri lanka: an econometric analysis - Neerthana, G.; Vijayakumar, S. (Proceedings of 9th International Symposium (Full Paper), 2019)
This study is to find out the impacts of macroeconomic variables such as foreign direct investment, money supply, international trade, and exchange rate after open economy policy and to analyze the long run relationship between these variables. The time series data of the variables such as economic growth rate, foreign direct investment, money supply, exchange rate, and international trade from 1977 – 2017 have been collected from Central Bank of Sri Lanka, World Bank Data Base, the Department of Census, and Web sites. To analyze the date, the statistical software, EVIEWS – 7 is used. Augmented Dickey Fully Test (ADF Test), multiple Regression, Multi colineartity test, Series correlation test, Johansen Test, Autocorrelation, Heteroscedasticity test are the tools used to analyze the data. All the variables used in this study are stationary. As per Model 1, foreign direct investment and money supply are significant to determine the economic growth. Accordingly, the changes by one million in foreign direct investment and money supply lead to change economic growth by 83.02 million and 70.46 million respectively. These variables influence on the economic growth by 90 percent. As per Model 2, there is a positive relationship between the dependent variable of economic growth and independent variables such as foreign direct investment, money supply, exchange rate, and international trade. These variables influence on economic growth by 93 percent. In addition, there is a long run relationship between these variables and the economic growth.
Keywords: foreign direct investment; money supply; exchange rate; economic growth; open economy